Early Outcomes of a High PaO2/FiO2 Ratio during Cardiopulmonary Bypass - Hülya Yilmaz AK; Yasemin Özşahin; Mehmet Ali Yeşiltaş; Baris Sandal; Ziya Salihoglu; Kerem Erkalp (Journal of Tehran University Heart Center, 2022)
Background: In cardiac surgery, supraphysiological oxygen levels are frequently applied perioperatively. In this study, we examined the postoperative effect of perioperative hyperoxemia in cardiac surgery.